Peranan Serasah Terhadap Sumbangan N dan P pada Agroekosistem Kopi - RUSDI EVIZAL; TOHARI TOHARI; IRFAN D. PRIJAMBADA; JAKA WIDADA (Agrotrop : Journal on Agriculture Science, 2012)
Litter is the main source of organic matter and nutrient entrance in shade grown coffee agroecosystems.Shade trees provide ecological and economic benefits in coffee agro-ecosystems thatindicate the key factor for sustainable coffee production. This study examined the role of litter onnutrient (N and P) returning in coffee agro-ecosystems. The experimental plots of Coffea canephorawere constucted at benchmark site of Conservation and Sustainable Management of Below-GroundBiodiversity (CSM-BGBD), in Sumberjaya Subdistrict, West Lampung, Indonesia, during 2007-2010.Types of shade trees to be examined were legume shade trees of Gliricidae sepium and Erythrinasububrams, non-legume tree of Michelia champaca, and no shade tree. The results showed that: (1)kind of shading determined litter productivity of coffee agro-ecosystems. Litter productivity of coffeeagro-ecosystems with shade trees increased coffee bean yield, (2) litter was an important source of Nand P that returned into the soil. Amount of nitrogen from litter biomass has linier effect on coffee beanyield.